ANALISIS RANCANGAN SOP PEMESANAN MENU PADA SISTEM POINT OF SALES YOKKEBIZ DI WARUNG YEAH! - Sihite, Hetty Yulianti; Yoe, Natalia; Lee, Cellyn Vienna; Jefri (JURNAL MATA PARIWISATA, 2025)
Standard Operating Procedure (SOP) is a crucial element in business operations that ensures consistency and efficiency. This study was conducted at Warung Yeah! in the Lagoi Tourism Area to analyze the current ordering system and propose a written SOP for improvement. Data collection techniques included interviews, observations, and documentation. The analysis used a qualitative descriptive approach to summarize findings, identify issues, and propose digital solutions. Results show that Warung Yeah! currently lacks a written SOP, and the manual order-taking system leads to inefficiencies. By integrating digital solutions with the YokkeBiz POS system, this study aims to enhance service quality, staff efficiency, and customer satisfaction